2017
DOI: 10.4103/ijo.ijo_880_16
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of deep anterior lamellar keratoplasty following autologous simple limbal epithelial transplant in pediatric unilateral severe chemical injury

Abstract: Aims:To evaluate outcomes of deep anterior lamellar keratoplasty (DALK) in pediatric eyes with unilateral severe chemical injury which have undergone autologous simple limbal epithelial transplant (SLET).Settings and Design:The study design was a retrospective case series.Materials and Methods:This retrospective, case series of all children <16 years of age that have undergone DALK following autologous SLET procedure in unilateral severe chemical injury evaluates the outcomes and complications in the setting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Gupta et al reported an anatomical success of 85% and visual success of 57% at 6 months after PKP performed after SLET. Another study by Singh et al 26 described the outcomes of deep anterior lamellar keratoplasty in eyes after SLET in the pediatric age group after chemical injury. They observed failure of corneal allograft in 27% of eyes and visual improvement of >2 lines in 54% eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported an anatomical success of 85% and visual success of 57% at 6 months after PKP performed after SLET. Another study by Singh et al 26 described the outcomes of deep anterior lamellar keratoplasty in eyes after SLET in the pediatric age group after chemical injury. They observed failure of corneal allograft in 27% of eyes and visual improvement of >2 lines in 54% eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al have reported maintenance of clear graft at 15 months post-PK in eyes previously treated with SLET in 85% of patients (11). Similarly Singh et al reported anatomical success in 72% of the eyes and visual acuity improvement in 54% of the eyes undergoing DALK post-SLET (27).…”
Section: Analysis Of Existing Evidence On Slet In Regenerating the Human Corneal Epitheliummentioning
confidence: 95%
“…The outcomes of sequential secondary surgeries such as PK and deep anterior lamellar keratoplasty (DALK) after SLET were also reported. [2526] In seven eyes of seven patients who underwent PK 9.5 ± 11.9 months after SLET, six eyes maintained a clear graft at 15.1 ± 5.4 months after PK. [25] Another report of 11 eyes of children who underwent DALK following SLET for unilateral severe chemical injury with LSCD with follow-up of 13 ± 4.6 months following DALK reported anatomical success in 8 (72%) eyes and visual acuity improvement in six (54%) eyes.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…[25] Another report of 11 eyes of children who underwent DALK following SLET for unilateral severe chemical injury with LSCD with follow-up of 13 ± 4.6 months following DALK reported anatomical success in 8 (72%) eyes and visual acuity improvement in six (54%) eyes. [26]…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation